2007
DOI: 10.1080/00498250701463325
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of desloratadine in healthy volunteers

Abstract: The absorption, metabolism and excretion of desloratadine (DL, Clarinex) were characterized in six healthy male volunteers. Subjects received a single oral 10-mg dose of [(14)C]DL ( approximately 104 microCi). Blood, urine and feces were collected over 240 h. DL was well absorbed; drug-derived radioactivity was excreted in both urine (41%) and feces (47%). With the exception of a single subject, DL was extensively metabolized; the major biotransformation pathway consisted of hydroxylation at the 3 position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…gov/drugsatfda_docs/label/2001/21165lbl.pdf). These results strongly suggest that hepatic metabolism is responsible for the formation of 3-hydroxydesloratadine and are consistent with the urinary and biliary excretion of this metabolite (and its O-glucuronide) in humans (Ramanathan et al, 2006(Ramanathan et al, , 2007. Data on the metabolism of desloratadine in nonclinical species are limited, with 5-hydroxydesloratadine and 6-hydroxydesloratadine reported as the major excreted metabolites in mice, rats, and monkeys.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…gov/drugsatfda_docs/label/2001/21165lbl.pdf). These results strongly suggest that hepatic metabolism is responsible for the formation of 3-hydroxydesloratadine and are consistent with the urinary and biliary excretion of this metabolite (and its O-glucuronide) in humans (Ramanathan et al, 2006(Ramanathan et al, , 2007. Data on the metabolism of desloratadine in nonclinical species are limited, with 5-hydroxydesloratadine and 6-hydroxydesloratadine reported as the major excreted metabolites in mice, rats, and monkeys.…”
Section: Discussionmentioning
confidence: 87%
“…The major in vivo human active metabolite of desloratadine is 3-hydroxydesloratadine, which is subsequently glucuronidated to 3-hydroxydesloratadine O-glucuronide. Both are excreted in roughly equal amounts in urine and feces (Ramanathan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…20). The intrinsic potency of desloratadine far exceeds that of the parent (Anthes et al, 2002), the free fraction is higher by 5-fold, and the circulating concentrations are also higher (Ramanathan et al, 2007). When these three factors are combined, it suggests that loratadine itself is responsible for none of the in vivo antihistaminic activity.…”
Section: A Drugs With Active Metabolites That Dominate the Activitymentioning
confidence: 94%
“…In humans, desloratadine is converted to 3-hydroxydesloratadine (by hydroxylation of the pyridine ring) followed by O-glucuronidation to 3-hydroxydesloratadine O-glucuronide. Both 3-hydroxydesloratadine and its O-glucuronide conjugate are major in vivo metabolites excreted in approximately equal amounts in urine and feces (Ramanathan et al, 2007).Conventional in vitro systems such as recombinant P450 enzymes, human liver microsomes (HLM), and human liver S9 fractions do not convert desloratadine to 3-hydroxydesloratadine; hence, its enzymology and the basis for certain individuals being identified as poor metabolizers of desloratadine have remained a mystery for many years (Prenner et al, 2006;Ghosal et al, 2009). Previously, we demonstrated that cryopreserved human hepatocytes (CHH) can form 3-hydroxydesloratadine, as can HLM provided they are supplemented with both NADPH and UDPglucuronic acid (UDP-GlcUA) (Kazmi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%